Empirical Effect: Flipped Classroom-Based E-Learning to Face Learning on Covid-19 Pandemic - Sakti, Rizki Hardian; Sukardi, Sukardi (Jurnal Pendidikan dan Pengajaran, 2021)
At the COVID-19 pandemic era in 2019-2020, all schools in the world faced a chalenging education situation. Innovative solutions were needed to optimize education efforts thus flipped classroom-based e-learning was implemented to maintain social distancing. The purpose of this study was to see the effectiveness or the empirical impact of the application of flipped classroom-based e-learning during the COVID-19 period. This study used a deductive approach using a choice of quantitative methods. The sample in this study was 30 students of SMKN 5 Padang. The instrument used in cognitive assessment was a test, while the effective and psychomotor assessment used an assessment rubric. We found that flipped classroom-based e-learning was effectively used in the learning process during the COVID-19 pandemic. Therefore, the flipped classroom-based e-learning can be effectively used as a media for distance learning.